Comparison of Results of Primary Repair Versus Ileostomy in Enteric Fever Ileal Perforation in Different Gender Groups - Ajmal Khan Bazai, Ahmad Zeb, Muhammad Umar, Muhammad Hanif, Abdul Latif, Jamshed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Processes of Ileostomy in patient having Enteric fever perforation with friable gut defunctions the diseased gut, change the route of the infected fecal matter, protects the intestinal repair done in septic tissues and reduces the anastomotic dehiscence. Disadvantage is that it needs further surgery for its closure, leads to Ileostomy related complications. Method: A Randomized controlled study. At BMC Hospital Bolan Quetta Started in November 2015 to May 2016. Our objectives were to compare post-operative wound infection between primary closure and Ileostomy in patients undergoing surgery for Enteric fever ileal perforation. Total One Hundred and Fifty patients who underwent Enteric fever perforation surgery were included. The surgical treatment was done as primary repair (group-A) and Ileostomy (group-B). Post-operative complications like wound infection and wound intra abdominal abscess were evaluated till 5 days of hospital stay. Comparison between 2 groups was done using chi square. Stratification was done and p-value ≤0.05 was considered as significant. Results: In group-A 47 maless and 28 femalesss and in group-B 52 maless and 23 femalesss patients were included. In group-A, 40% observed wound discharge while in group-B it was 24%. In group-A, acceptable comesis were observed for 80% cases and in group-B, it was 93.3%. Results showed significant association of wound discharge and acceptable cosmesis with the 2 study groups. Conclusion: Better results in Ileostomy group than primary repair group was significant observed in the study. Keywords: Enteric fever , Acceptable cosmesis, Wound Discharge, Intra Abdominal Collection, Ileostomy, Enteric fever Ileal Perforation